2009
DOI: 10.1108/13673270910931143
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge transfer between globally dispersed units at BMW

Abstract: Purpose -Building on the social network view and new product development perspective, the purpose of this paper is to examine how knowledge is transferred between identical, yet geographically distant units within a multinational corporation.Design/methodology/approach -An embedded case study of Bayerische Motoren Werke (BMW) examining core drivers that impact on inter-unit knowledge transfers between six events and exhibitions (E&E) units located in Europe, Asia, and Australasia.Findings -The data highlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 91 publications
(157 reference statements)
0
12
0
Order By: Relevance
“…There are many researches conducted in the area of knowledge management and knowledge transfer/ sharing within an organization (e.g. Nesheim & Gressgard, 2014, Frank & Ribeiro, 2014, Fang, Yang & Hsu, 2013, Schleimer & Riege, 2009 as this topic is critical from many perspectives, e.g. competitiveness in the market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many researches conducted in the area of knowledge management and knowledge transfer/ sharing within an organization (e.g. Nesheim & Gressgard, 2014, Frank & Ribeiro, 2014, Fang, Yang & Hsu, 2013, Schleimer & Riege, 2009 as this topic is critical from many perspectives, e.g. competitiveness in the market.…”
Section: Discussionmentioning
confidence: 99%
“…Patriotta, Castellano, and Wright (2013) bring other and similar perspective: "The high-level managers recognized the benefits of knowledge transfer as a way to avoid duplication of efforts, reduce time and energy in accessing information and ready-made solutions, learn from others' best ways of doing things, and achieve global scale efficiency." There were some researches identifying the most efficient or important channel of knowledge transfer between universities and industry (Bekkers & Bodas Freitas, 2008), between countries (Marcon, 2012or Schleimer & Riege, 2009, between projects (Frank & Ribeiro, 2014) or within strategic alliances (Walter & Lechner & Kellermanns, 2007). Their findings usually stay on higher level, e.g.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…While several aspects of distance have been extensively discussed in the international business literature, geographical and cultural distance are the two main dimensions of distance shown to play a major role in international business activities. Geographical distance (also called physical distance or spatial distance) is shown to have a significant effect on MNC's strategic decisions including cross-border joint venture (Zaheer and Hernandez 2011) and globally dispersed units (Schleimer and Riege 2009). The research found that geographical distance among globally dispersed activities results in difficulties in coordination and communication between teams and, hence, creates a barrier in the transfer of knowledge and innovation across teams ( Ambos and Ambos 2009;Chen and Lin 2018;Hansen et al 1999).…”
Section: Global Dispersion Of Value Chain Activitiesmentioning
confidence: 99%
“…All in all, a moderate level of spacing between teams and groups in complex social systems seems optimal in promoting interaction. 80 81 Too many gaps or too wide the spacings between groups can indicate disunity or disintegration, which makes it hard to enhance linkages. Too few gaps, and narrowness increases the risk of poorly formed localised identities or the system being overconstrained, with no breathing space between the team or group.…”
Section: Discussionmentioning
confidence: 99%